PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA, DAN KEPEMIMPINAN TERHADAP KINERJA DI CV EJS GROUP - Dita Ratna Purnami; Lamidi Lamidi; Sunarso Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
This research was conducted to: 1) Analyze the significance of the influence of the work environment on employee performance 2) Analyze the significance of the influence of work motivation on employee performance 3) Analyze the significance of leadership influence on employee performance in CV EJS Group. This research is a survey research conducted directly and this study uses primary data from questionnaire answers shared with all employees at CV EJS Group. The study sampled 37 employees. Data analysis techniques use multiple linear regression analysis. T test results calculate the work environment has a positive and significant impact on employee performance. The results of t calculate work motivation have a positive and significant effect on employee performance. The results count leadership's negative and insignificant impact on employee performance. F test results calculate simultaneously free variables (work environment, work motivation and leadership) have a significant effect on bound variables (employee performance). The results of the determination coefficient test showed the effect of work environment variables, work motivation and leadership on employee performance at CV EJS Group was 30.9%, while the remaining 69.1% was influenced by other unreviewed variables.